Radioiodine Accumulation in a Giant Ovarian Cystadenofibroma Detected Incidentally by 131-I Whole Body Scans - Mohammed Mebarki; Abdelghani Menemani; Abdelkader Medjahedi; Fouad Boualou; Abdelhak Slama; Sarah Ouguirti; Fatima Zahra Kherbouche; Nécib Berber (Case Reports in Radiology)
Ovarian cystadenofibroma is a relatively rare tumor; it is usually asymptomatic and is found incidentally. We present the case of a 24-year-old female patient, who had undergone total thyroidectomy for thyroid papillary carcinoma, with an asymptomatic giant cystadenofibroma, incidentally discovered by diagnostic 131I-SPECT/CT WBSs. We summarize the clinical history, imaging data, and histopathological study on a rare case of radioiodine accumulation in cystadenofibroma, and we discuss the mechanism of uptake of radioiodine in this case.